Pengaruh Kualitas Produk, Nilai Pelanggan (Customer Value) Terhadap Kepuasan Pelanggan Pada Krupuk Rambak Kulit Sapi Magetan (Studi Kasus pada Pelanggan Perusahaan Krupuk Rambak Kulit Sapi Cap Sapi Lancar di Desa Mojopurno Kota Magetan) - Matheous Tamonsang; Elita Ahsana Amalia (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2021)
The business world in this era continues go through increasingly more advanced developments. this could be due to increasingly competitive business competition. In fulfilling customer satisfaction, that is, if the quality of the product to be provided by the company is in accordance with the wishes of the customer, entrepreneurs can be increased their market share through quality fulfillment by providing product excellence and customer value. Customer satisfaction can be created through product quality, customer value (customer value) provided to customers. This study discusses customer satisfaction at the COWCAR branded Cowskin Rambak Krupuk Company in Magetan. This study tested two independent variables, namely product quality and customer value which can affect the dependent, namely customer satisfaction. This research was conducted by using a questionnaire method to 123 customer respondents of the Cattle Skin Crackers Rambak Company with SAPI LANCAR stamp. Data collection techniques in this study using purposive sampling method and non-probability sampling method. This study uses multiple linear regression analysis for its data analysis technique, where the results show that product quality has a significant effect with a value of 0.027 and customer value has a significant effect with a value of 0.000 on customer satisfaction.